New solid forms of itraconazole and their pharmaceutical applications - CRUZ, RICARDO MACHADO (Trinity College Dublin. School of Pharmacy & Pharma. Sciences. Discipline of Pharmacy, 2020)
Itraconazole (ITR) is an active pharmaceutical ingredient (API) with a broad-spectrum antifungal activity. This API has a very low solubility, which can hinder its bioavailability after oral administration. In this work, approaches such as bottom-up nanonisation, PEGylation of nanoparticles (NPs), cocrystallisation and nano-cocrystallisation were produced and assessed regarding their potential to improve the pharmaceutical properties of ITR. As regards nanonisation, evaluation of the variables involved in the heat induced evaporative nanoprecipitation (HIEAN) of ITR revealed that the antisolvent:solvent (AS:S) ratio was a critical parameter affecting the particle size of the dispersions. Since changes in this parameter involved altering both solvent volume and the final concentration of ITR, thus affecting the supersaturation degree. The antisolvent temperature was only critical when used at values higher than the boiling point of acetone (>56 °C), affecting the supersaturation due to an increased rate of acetone evaporation. The inclusion of a residual solvent (acetone) evaporation step had no impact on the particle size of the ITR dispersions, however, when used for a prolonged time, it resulted in crystallisation of the particles. The ITR dispersions evaporated for 40 min at 50 mbar showed an enhanced colloidal stability when stored at 4 and 25 °C. The ITR NPs produced with the optimised HIEAN conditions, i.e. the antisolvent phase at 80 °C and the AS:S ratio of 10:1, yielded a monodispersed dispersion with the particle size of 253 ± 16 nm, which had solid-state characteristic of a liquid crystal smectic mesophase. The following polymers: poly(ethylene glycol) (PEG) and 4-arms PEG (4 ARM) with a molecular weight of 10 kDa were the most suitable candidates for PEGylation of ITR NPs. The modified NPs had sizes below 500 nm. The evaluation of the mucoadhesive properties of PEG, poly(ethylene glycol) methyl ether (MPEG) and 4 ARM PEG (all with a molecular weight of 10 kDa) showed that these polymers interacted weakly and reversibly with mucin, despite being used at high concentrations of 10, 50 and 100 mg/mL. The non-PEGylated and PEGylated ITR NPs produced using the optimised HIEAN method had similar average particle sizes and polydispersity indices, although the PEGylated NPs had their zeta potential partially neutralised, reducing their stability in dispersion. The non-PEGylated ITR NPs were isolated as a smectic mesophase, while the PEGylated NPs were more crystalline. As evidenced by scanning electron microscopy, the morphology of a number of the PEGylated samples was affected by the polymer presence and the systems were composed by a mix of spherical and flake-like particles, instead of the spherical particles as in the non-PEGylated ITR NPs. The non-PEGylated ITR NPs were considered as having a mucopenetrative potential, as the investigation of the mucoadhesive properties revealed no evidence that these particles could strongly interact with mucin. On the other hand, the PEGylated NPs exhibited mucoadhesive potential in stationary conditions, but when flow conditions were applied the particles had mucopenetrative properties. The screening for multicomponent forms of ITR identified one new cocrystal produced using terephthalic acid (TER) and eutectic phases with dihydrocaffeic acid, 4-nitrobenzoic acid and the 4-aminosalicylic acid. The single crystal X-ray analysis revealed that the crystalline structure of the new cocrystal (ITR-TER) had a 2:1 stoichiometry. The ITR molecules are in an anti-parallel arrangement with the coformer 'trapped' in the space formed between the two ITR molecules. This supramolecular arrangement was stabilised by H-bonds formed between the hydroxyl moiety of the carboxyl acid group and the N4 of the azole ring of ITR while the C3 of the azole group and the carbonyl group of the coformer formed an additional H-bond. The dissolution behaviour of the freeze dried ITR (FD ITR) showed a remarkable improvement considering its intrinsic dissolution rate (IDR) and powder dissolution in comparison to crystalline ITR. Considering the ITR cocrystals with oxalic acid (ITR-OXA), succinic acid (ITR-SUC) and TER, the IDR values and powder dissolution profiles correlated with the aqueous solubility of the coformers. The presence of polymers in the dissolution media prevented the conversion of FD ITR, ITR-OXA and ITR-SUC to crystalline ITR. The conditions to produce the nano-cocrystals (NCCs) of ITR-TER using the method of antisolvent precipitation were investigated. A mixture of acetone and methanol in a volume ratio of 70:30 (v/v) enabled ITR and TER solubilisation at the highest concentration respecting the cocrystal stoichiometry. Lecithin was used as a stabiliser at 5% (w/w) of the total solid content in the ITR-TER dispersions resulting in monodispersed particles with smaller sizes and lower zeta potential values in comparison to the batch made without lecithin. The ultrasound application to the ITR-TER dispersions reduced the particle sizes when sonication was applied continuously for at least 15 min. Modifications of the method setup was successful to increase the batch size by a 5-fold without affecting the characteristics of the ITR-TER dispersions. Trojan particles, nano-in-microparticles, produced by spray-drying of ITR-TER NCC with mannitol (MAN), raffinose and trehalose were composed of spherical particles and could be instantaneously redispersed in water releasing the NCCs. The released NCCS has particle sizes smaller than 250 nm as measured by nanoparticle tracking analysis. The median particle size of ITR-TER-MAN was 4.85±0.06 μm, in agreement with the results obtained from the next generation impactor, as the mass median aerodynamic diameter and geometric standard deviation of this sample was 4.02±0.13 μm and 1.74±0.03, respectively. This enabled ITR-TER-MAN to have the largest respirable fraction, of 36.11 ± 0.17%. This indicated that a larger fraction of ITR-TER-MAN could be deposited in deeper regions of the lungs.
APPROVED
Keywords: Itraconazole; Cocrystals; Nanoparticles; Mucoadhesivity; Liquid Crystal; Nanococrystal; Pulmonary Delivery; Terephthalic Acid; PEGylation; Poly(ethylene glycol)